Transformasi Kinerja Pegawai Melalui Kepemimpinan Lurah di Kantor Kelurahan Rimuku, Mamuju: Sebuah Tinjauan Pelaksanaan Pembangunan - salman, Rara novrayanti; Zainuddin, Muhlis (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This study aims to evaluate the impact of Lurah leadership on employee performance in the implementation of development in Rimuku Village, Mamuju. The population consists of Civil Servants, neighborhood chiefs, and 64 people. The sample was selected using Saturated Sampling due to the relatively small population size. Data were collected through questionnaires and interviews, then analyzed in a qualitative descriptive manner. The results showed that Lurah's leadership style had a positive effect on development, as well as employee performance. In addition, the combination of Lurah's leadership style and employee performance also has a positive impact on development in Rimuku Village, Mamuju.